Integrated photovoltaic storage joint smoothing strategy based on simultaneous perturbation stochastic approximation algorithm - Yujing, He; Jie, Chen; Xueqin, Tian; Yafei, Wang (Frontiers in Energy Research, 2023)
In order to realize the real-time control of smooth grid connection of Photovoltaic power generation and energy management of hybrid energy storage systems under the condition that the energy storage equipment can operate safely,a control strategy combining simultaneous perturbation stochastic approximation(SPSA) and rule control is designed.Firstly, the photovoltaic data are processed and the data features of power slope are extracted, and then the grid-connected reference power is obtained by simultaneous perturbation stochastic approximation algorithm.Secondly, considering the state of charge (SOC) of the energy storage device and the safe operating power range of the hydrogen storage device, 24 kinds of rules are formulated to distribute the mixed storage power through the method of rule control.Finally, according to the ten seconds sampling data of a typical day, the simulation is carried out on Matlab platform, and compared with the first-order low-pass filtering algorithm. The results show that the simultaneous perturbation stochastic approximation algorithm has a strong smoothing ability, and the rule control can also be assigned according to the characteristics of the hybrid storage equipment under the condition of ensuring its normal operation.